PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID DENGAN MENGGUNAKAN APLIKASI APPY PIE PADA MATA PELAJARAN INSTALASI PENERANGAN LISTRIK - Putri Kanti Wigati; Hamonangan Tambunan (Universitas Negeri Medan, 2023)
Abstract The research aims to determine the feasibility and effectiveness of developing android-based media using the Appy Pie application on the subject of electrical lighting installations. This study uses the Research and Development (R&D) method with the development procedure used referring to the ADDIE model developed by Dick and Carry (1996) which includes analysis, design, development, implementation and evaluation. The subjects of this study were students of class XI TITL SMK N 13 Medan. The feasibility of the developed media refers to media experts with a score of 93% in the